Association between depression, anxiety, stress, social support, resilience and internet addiction: a structural equation modelling - Taş, İbrahim (Institute of Education Science (ERIC), 2019)
The objective of this study is to test whether depression, anxiety, stress, social support and resilience have a significant effect on predicting internet addiction in university students. For this purpose, the pattern of the associations between the variables was examined. The study was conducted on 349 students attending two different universities during the 2018‐2019 Academic Year. In the study, Personal Information Form, Depression, Anxiety Stress Scale, Internet Addiction Scale, Perceived Social Support Scale and Resilience Scale were used to collect data. First of all, whether the data were normally distributed was tested. The data, which were found to be normally distributed, were analyzed with correlation and structural equation modelling and SPSS 25 and AMOS 25 programs were used to analyze data. Significant negative association was found between internet addiction and depression, anxiety and stress. Significant negative association was found between internet addiction and social support and resilience. Significant positive association was found between social support and resilience. Fit indices, regression coefficients and variance values of the model were found to be significant. The variables were found to explain 25% of the variance in internet addiction. It was found that the proposed theoretical model to explain internet addiction was confirmed and the results obtained were in parallel with the literature.
Keywords: Internet addiction; Depression; Anxiety; Stress; Social support; Resilience